The relationship between the UDP and the Arabs until the beginning of the First World War - علاء الدين , إبراهيم; العليوي, عبد الحميد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
National awareness intensified in the Arab environment, and began to express itself in word and deed, as the demand began explicity to improve the political situation of the Arabs within the framework of the ottoman Empire, and with the developments of the situation, and according to the political situation in the ottoman Empire, those demands turned in to movement and overt political activity that extended to different ideological directions. And geographically, the Arabs tried to demand reforms within the ottoman Empire after the issuance of the ottoman constitution in 1908, This was to protect their country from the developments occurring within the ottoman Empire and their requirement of decentralized rule within the state, but they clashed with the Turanian policy of the Union and progress party, which formulated the last role in the ottoman Empire and received the actual rule in it, denouncing the role of Arabs in political life in the ottoman state and their role in disrupting its internal conditions, through their participation in secret and public associations and demanding new privileges in the ottoman Empire, which contradicts the policy of the Union and progress Association based on leaving all elements under the banner of the ottoman Empire and preventing any non-Turkish element from receiving any position in the institutions of the ottoman empire.